Identification of Competencies and Teaching Models for the Governance of Smart Sustainable Cities in the South American Context - Sanchez Ortiz, Aurora (2020)
This study is developed in the context of the Strengthening Governance Capacity for Smart Sustainable Cities (CAP4CITY) Project, part of the Erasmus + Programme. The study aims to support the design of teaching materials to address the human-capacity related needs for the governance of Smart Sustainable Cities (SSC) in South America. This article identifies the competencies and instructional design for the design of smart sustainable cities courses adapted to the South American context. Applying a scenario-building approach and the CAP4CITY roadmap for smart sustainable city initiatives, we conducted two workshops in Chile and two in Argentina attended by representatives from academia, NGOs, government agencies, and private companies. Using the data about competencies and teaching models gathered during these events, the study clustered the data and identified the major areas of competences and instructional methods. Lastly, we compared the results from both countries.